Midterm to long‐term safety and efficacy of self‐expandable nitinol stent implantation for coarctation of aorta in adults. Issue 3 (14th July 2017) - Haji Zeinali, Ali Mohammad; Sadeghian, Mohammad; Qureshi, Shakeel A.; Ghazi, Payam
Abstract: Purpose: Endovascular treatment of coarctation of aorta (CoA) by self‐expandable Nitinol stents is one of the recognized treatment methods and may be an alternative to surgery or balloon‐expandable stent implantation for CoA but there is little information about midterm to long term results of self‐expandable stents. Methods: Sixty‐two patients with CoA (40 men), with a mean age of 30.7 ± 11 years, (range 17–63 years) underwent stent implantation with Optimed self‐expandable Nitinol stents between 2005 and 2014. Successful outcome was defined as peak systolic pressure gradient ≤20 mmHg after stent implantation. The patients were followed‐up clinically and by echocardiography and in patients, in whom there was suspicion of recoarctation, CT angiography or recatheterization was performed. Results: 65 stents were successfully implanted in all 62 patients. Peak systolic pressure gradient decreased from mean 62.4 ± 18 mmHg (range 35–100 mmHg) to mean 2.8 ± 5 mmHg (range 0–15 mmHg; P < 0.001). Stent displacement occurred in 3 patients during the procedure. These were managed successfully by an overlapping second stent. None of the patients had major complications such as aortic dissection, rupture, or vascular access problems. In follow up, only three patients had recoarctation, and two of these were managed successfully by balloon redilation or further stenting 16 and 18 months after the first procedure and one patient refused reintervention. There were two deaths, unrelated to the procedure, 12 and 78 months after the initial intervention. Follow‐up of a mean of 45.5 ± 17 months (range 12–105 months) demonstrated no evidence of aneurysm formation or stent fracture. Conclusions: Self‐expandable nitinol stents for the treatment of native and recurrent CoA is safe and has good efficacy with acceptable midterm to long‐term outcome.